POSTERIOR REVERSIBLE ENCEPHALOPATHY SYNDROME AFTER EXCESIVE AMINO-ACID PARENTERAL NUTRITION-CASE REPORT - Bushinovska, Jasna M.; Ognjenovic, Ljubomir; Lazareska, Menka; Zafirova, Dina; Asani, Elmedina; Bushinoska-Ivanova, Gabriela (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
Posterior reversible encephalopathy syndrome (PRES) is a reversiblesubacute neurologic state that despite other causes, such as immunosuppression, chemotherapy, sepsis, preeclampsia, renal failure, transplantation, autoimmune disorders, can occur as a result of a toxic effect of some drugs or medications. Uncontrolled hypertension results in loss of cerebral autoregulation, vasogenic edema and neurologic signs and symptoms such as severe headaches, visual disturbances, seizures, confusion, somnolence and sometimes loss of consciousness. The condition is usually self-limiting, but reversibility depends on the early recognition and fast removal of the toxic agent, as a trigger of the disorder. Here, we present a case of a 53 year old patient who presented himself at our clinic in a septic state of abdominal origin. He underwent an abdominal surgery, afterwards he received a combination of strong antibiotics according to microbiologal findings, supportive therapy and parenteral nutrition as his state demanded. Septic state, antibiotic therapy and high rates of amino acid infusion for parenteral nutrition resulted in neurologic disturbance during the treatment. CT scan and MRI of the brain stated the diagnosis of PRES. Late recognition and uncontrolled prolonged aggressive parenteral amino acid infusion were the most probable reasons for fast deterioration, consecutive brain damage and the patient’s death. Keywords: Posterior reversible encephalopathy syndrome, hypertension, neurologic deficit, vasogenic edema, high-rate parenteral nutrition. https://doi.org/10.55302/JMS2143106b